The Effectiveness Of Public Service Training For Internalizing Nationalism Values Based On Local Wisdom: Enhancing Apparatus Professionalism Nagari In West Sumatra Province - Luqmanul Hakim; Widia Sri Ardias; Sefri Auliya; Nur Aisyah Yusri (Fakultas Sains dan Teknologi, 2023)
The evaluation results of the quality of public services carried out by officials in one of the villages in West Sumatra are perceived by the community as being full of discrimination. This is due to the lack of nationalism in the Nagari apparatus, so the apparatus is perceived as unprofessional in carrying out its function as a servant for the community. This research was conducted with an experimental approach using a pretest-posttest group design model (Creswell, 2012). Participants were given public service training with the main material on internalizing the values of nationalism, and then their knowledge and attitudes about nationalism were measured before and after the training. The sample for this study was 63 nagari officials from 3 different villages in West Sumatra, namely Nagari Gunung Talang, Solok Regency; Nagari Kota XI Tarusan, Pesisir Selatan Regency; and Nagari Pariangan, Tanah Datar Regency. The data processing technique used different analyses with paired sample t-tests. The results of the data analysis prove that public service training is effective in increasing participants' knowledge and attitudes toward nationalism, as evidenced by the index p 0.05. It is recommended that this training be carried out consistently to maintain the quality of public services in the community. Keywords: Nasionalism, Nagari, Public Service Training